Concentrate supplementation improves cold-season environmental fitness of grazing yaks: responsive changes in the rumen microbiota and metabolome - Yi, Simeng; Wu, Hao; Liu, Yue; Dai, Dongwen; Meng, Qingxiang; Chai, Shatuo; Liu, Shujie; Zhou, Zhenming (Frontiers in Microbiology, 2023)
Yak (Bos grunniens) is an important economic animal species on the Qinghai-Tibet Plateau.Yaks grazed in the cold season often suffer from nutritional stress, resulting in low production performance. This situation can be improved by properly feeding the grazing yaks in the cold season; however, there is still little information about the effect of different feeding levels on the intestinal microflora and metabolites of yaks. Therefore, this study aimed to explore the effect of feeding different doses of concentrate supplements on rumen bacterial communities and metabolites in grazing yaks during the cold season. Feed concentrate supplementation significantly improved the production performance and rumen fermentation status of grazing yaks during the cold season, and switched the type of ruminal fermentation from acetic acid fermentation to propionic acid fermentation. Ruminal fermentation parameters and ruminal bacterial abundance correlated strongly.At the phylum level, the abundance of Firmicutes increased with increasing concentrate supplementation, while the opposite was true for Bacteroidota. At the genus level, the abundance of Christensenellaceae_R-7_group, NK4A214_group, Ruminococcus, norank_f__Eubacterium_coprostanoligenes_group, norank_f__norank_o__ Clostridia_UCG-014, Lachnospiraceae_NK3A20_group, Acetitomaculum, and Family_XIII_AD3011_group increased with increasing concentrate supplementation, while the abundance of Rikenellaceae_RC9_gut_ group decreased. Dietary concentrate supplementation altered the concentration and metabolic mode of metabolites in the rumen, significantly affecting the concentration of metabolites involved in amino acid and derivative metabolism (e.g., L-aspartic acid, L-glutamate, and L-histidine,), purine metabolism (e.g., guanine, guanosine, and hypoxanthine), and glycerophospholipid metabolism (e.g., phosphatidate, phosphatidylcholine and phosphocholine), and other metabolic pathways. The strong correlation between yak rumen microorganisms and metabolites provided a more comprehensive understanding of microbial community composition and function. This study showed significant changes in the composition and abundance of bacteria and metabolites in the rumen of cool season grazing yaks fed with concentrate supplements. Changes in ruminal fermentation parameters and metabolite concentration also showed a strong correlation with ruminal bacterial communities. These findings will be helpful to formulate supplementary feeding strategies for grazing yaks in the cold season from the perspective of intestinal microorganisms.